The authority of Holy Scripture: an inaugural address - Briggs, Charles A. (Briggs heresy case, 1891)
I. The establishment of the chair by the directors of the seminary in accordance with the endowment of Charles Butler, LL.D; and the choice of the incumbent, Prof. Charles A. Briggs, D.D.--II. The inauguration services.--III. The inaugural address, on The authority of Holy Scripture.--IV. The position and importance of biblical theology.